PENGARUH FUNDAMENTAL TERHADAP RISIKO SISTEMATIS (BETA) DI ERA COVID PADA SAHAM SYARIAH TERTINGGI (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to examine and analyze the effect of fundamentals on systematic risk (beta). This study uses quantitative data using secondary data in the form of financial statements. the population used are companies that are included in the Jakarta Islamic Index (JII) list from 2018 to 2020 with a sample of companies that are included in the highest sharia shares in the covid era with a sample of 9 companies. Data management using SPSS version 22.0. The results showed that fundamental factors (debt to equity ratio, growth ratio, and return on assets) had a positive effect on systematic risk (beta).